Sonic hedgehog is Neuroprotective in the Cavernous Nerve with Crush Injury - Angeloni, Nicholas (2012)
INTRODUCTION: The cavernous nerve (CN) is commonly injured during prostatectomy, resulting in erectile dysfunction (ED). Although peripheral nerves have a limited ability to regenerate, a return of function typically does not occur due to irreversible down stream morphological changes in the penis that result from CN injury. We have shown in previous studies that sonic hedgehog (SHH) is critical for CN regeneration and improves erectile function after crush injury. AIMS: Examine a new direction, to determine if SHH is neuroprotective to the pelvic ganglia (PG)/CN after crush injury. A secondary focus is to examine if SHH signaling decreases with age in the PG/CN. METHODS: Sprague Dawley rats underwent bilateral CN crush and SHH and glial fibrillary acidic protein were quantified by western analysis of the PG/CN (n=6 rats at each time point) at 1, 2, 4, 7 and 14 days, and the apoptotic index was measured in the penis. SHH was quantified by western in the PG/CN with blockade of anterograde transport (n=4 rats) in comparison to mouse IgG (n=4 rats). If SHH is neuroprotective was examined at 4 (n=14 rats) and 7 days (n=16 rats) of treatment after CN crush. SHH protein was quantified in aging (P200-300, n=5 rats) PG/CN in comparison to normal adult (P115-120, n=3 rats) PG/CN. MAIN OUTCOME MEASURES: SHH pathway was examined in PG via immunohistochemistry, in situ, western and TUNEL. RESULTS: SHH is neuroprotective in the PG/CN with injury. SHH localization in the PG/CN suggests SHH interaction in neuronal/glial signaling. SHH protein is significantly decreased in the PG/CN after crush injury and in the aged PG/CN. Signals from the PG are required to maintain SHH in the CN. CONCLUSIONS: There is a window of opportunity immediately after nerve insult in which manipulation of SHH signaling in the nerve microenvironment can affect long-term regeneration outcome.